Transfusion of prion‐filtered red cells does not increase the rate of alloimmunization or transfusion reactions in patients: results of the UK trial of prion‐filtered versus standard red cells in surgical patients (PRISM A). (7th January 2013) - Elebute, Modupe O.; Choo, Louise; Mora, Ana; MacRury, Coral; Llewelyn, Charlotte; Purohit, Shilpi; Hicks, Vicky; Casey, Caroline; Malfroy, Moira; Deary, Alison; Reed, Tania; Meredith, Sarah; et al.
Summary: This study, conducted for the UK Blood Transfusion Services (UKBTS), evaluated the clinical safety of red cells filtered through a CE‐marked prion removal filter (P‐Capt™). Patients requiring blood transfusion for elective procedures in nine UK hospitals were entered into a non‐randomized open trial to assess development of red cell antibodies to standard red cell (RCC) or prion‐filtered red cell concentrates (PF‐RCC) at eight weeks and six months post‐transfusion. Patients who received at least 1 unit of PF‐RCC were compared with a control cohort given RCC only. About 917 PF‐RCC and 1336 RCC units were transfused into 299 and 291 patients respectively. Twenty‐six new red cell antibodies were detected post‐transfusion in 10 patients in each arm, an overall alloimmunization rate of 4·4%. Neither the treatment arm [odds ratio (OR) 0·93, 95% confidence interval (CI) 0·3, 2·5] nor number of units transfused (OR 0·95, 95% CI 0·8, 1·1) had a significant effect on the proportion of patients who developed new alloantibodies. No pan‐reactive antibodies or antibodies specifically against PF‐RCC were detected. There was no difference in transfusion reactions between arms, and no novel transfusion‐related adverse events clearly attributable to PF‐RCC were seen. These data suggest that prion filtration of red cells does not reduce overall transfusion safety. This finding requires confirmation in large populations of transfused patients.